TOXICOLOGICAL PROPERTIES OF THE DRUG «GLUDEZ» BASED ON GLUTARALDEHYDE - Omarbekova, U. Zh.; Umitzhanov, M.; Kushmukhanov, ZH. S.; Mussoyev, А. М. (ЗКАТУ им. Жангир хана, 2024)
Disinfection occupies a special place in the system of basic antiepizootic measures, as an element of a significant reduction in the total number of microorganisms and complete disinfection of pathogenic microflora at environmental facilities. In this regard, the search for new highly effective means for disinfection, prevention and treatment is currently especially relevant against the background of environmental changes in the environment. The analysis of the specialized literature shows that the process of creating new effective tools and technologies for their application is currently being activated [1-8]. Special requirements are imposed on disinfectants in order to prevent environmental pollution and ensure safety for people and animals. It is also important such quality as the convenience and simplicity of their use. In this regard, it is important to create and use effective disinfectants aimed at suppressing the viability of pathogenic microflora in environmental objects. At the same time, the toxicological evaluation of the disinfectant is the main criterion for the selection of promising drugs and the preparation of disinfectant compositions for introduction into veterinary practice. Signs of intoxication with the drug «Gludez» and the death of experimental animals strictly depended on the dose of the administered solutions of the drug under study, and the clinical picture of poisoning of white mice began to manifest itself 10-40 minutes after oral administration. At the same time, the average lethal dose (LD50) for white mice was 680 mg/ kg, and at a dose of 1030 mg / kg, the death of white mice occurred. Based on the data obtained, the drug «Gludez» according to the parameters of acute toxicity refers to medium toxic substances (hazard class III).
Omarbekova, U. Zh. Toxicological properties of the drug «gludez» based on glutaraldehyde / U. Zh. Omarbekova, M. Umitzhanov, ZH. S. Kushmukhanov, А. М. Mussoyev [et al.]. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - 2-1 (75). Ч. І. - Р. 211-219 (Uraksk).
Keywords: Gludez; dose; efficacy; disinfection; toxicity; allergy; mortality; mice; зкату; научный журнал